Heidegger's Understanding of Hermeneutics Facticity and his Contribution to Caputo's Cold Hermeneutics in his Work entitled Radical Hermeneutics - Anam, Rifqi Khairul (Sekolah Tinggi Filsafat Seminari Pineleng, 2025)
Current scholarship on Heidegger's hermeneutics of facticity often concentrates on its relationship to his broader ontology, such as Sheehan's examination of Ereignis as the